Overview of the fishery and aquaculture sectors in Malaysia - Obi, Chinedu; Brako Dompreh, Eric; Manyise, Timothy; Tan, Shau Hwai; Woo, Sau Pinn; Rossignoli, Cristiano (Frontiers Media SA, 2025)
This study presents a literature-based review of Malaysia’s fishery and aquaculture sectors, examining their historical development, production trends, contributions, and challenges. Unlike existing studies that focus primarily on production trends or environmental concerns, this paper provides a policy-oriented perspective, linking production challenges to governance, economic constraints, and gaps in small-scale aquaculture and private-sector involvement. The study show that in 2022, Malaysia’s total fishery production reached 1.89 million metric tons, with aquaculture contributing 30%. While capture fisheries have stagnated due to overfishing and environmental pressures, aquaculture has expanded, playing a crucial role in post-Covid-19 recovery. However, sustainability remains a challenge due to climate change, water pollution, rising production costs, and regulatory barriers. To address these issues, the study recommends promoting sustainable fishing and aquaculture practices, enhancing research and development (R&D), streamlining regulatory frameworks, improving disease management, and expanding economic support and market access. These measures are essential to strengthening Malaysia’s aquaculture sector and ensuring long-term food security and economic resilience.